Folk knowledge of invertebrates in Central Europe - folk taxonomy, nomenclature, medicinal and other uses, folklore, and nature conservation - Ulicsni, Viktor (J Ethnobiol Ethnomed, 2016)
BACKGROUND: There is scarce information about European folk knowledge of wild invertebrate fauna. We have documented such folk knowledge in three regions, in Romania, Slovakia and Croatia. We provide a list of folk taxa, and discuss folk biological classification and nomenclature, salient features, uses, related proverbs and sayings, and conservation. METHODS: We collected data among Hungarian-speaking people practising small-scale, traditional agriculture. We studied “all” invertebrate species (species groups) potentially occurring in the vicinity of the settlements. We used photos, held semi-structured interviews, and conducted picture sorting. RESULTS: We documented 208 invertebrate folk taxa. Many species were known which have, to our knowledge, no economic significance. 36 % of the species were known to at least half of the informants. Knowledge reliability was high, although informants were sometimes prone to exaggeration. 93 % of folk taxa had their own individual names, and 90 % of the taxa were embedded in the folk taxonomy. Twenty four species were of direct use to humans (4 medicinal, 5 consumed, 11 as bait, 2 as playthings). Completely new was the discovery that the honey stomachs of black-coloured carpenter bees (Xylocopa violacea, X. valga) were consumed. 30 taxa were associated with a proverb or used for weather forecasting, or predicting harvests. Conscious ideas about conserving invertebrates only occurred with a few taxa, but informants would generally refrain from harming firebugs (Pyrrhocoris apterus), field crickets (Gryllus campestris) and most butterflies. We did not find any mythical creatures among invertebrate folk taxa. Almost every invertebrate species was regarded as basically harmful. Where possible, they were destroyed or at least regarded as worth eradicating. However, we could find no evidence to suggest any invertebrate species had suffered population loss as a result of conscious destruction. Sometimes knowledge pertaining to the taxa could have more general relevance, and be regarded as folk wisdom concerning the functioning of nature as a whole. CONCLUSIONS: The high number of known invertebrate folk taxa suggests that it would be worth conducting further investigations in other areas of Europe.